Extended lag phase indicates the dormancy of biphenyl degrading Rhodococcus biphenylivorans TG9 under heat stress. (1st April 2023) - Fan, Jiahui; Feng, Jinsong; Xu, Dongdong; Li, Xinyi; Xu, Fengjun; Li, Haoming; Shen, Chaofeng
Abstract: Microbial remediation is a green and sustainable technology, but harsh environmental conditions could lead to microbial dormancy, such as entering a viable but non-culturable (VBNC) state. However, the evidence of VBNC is controversial and limited. In this study, heat stress (60 °C), one of the leading challenges for mesophilic degrading bacteria, was mimicked to investigate the physiological response of Rhodococcus biphenylivorans TG9. After 2 h of heat stress, the culturable TG9 cell count decreased from 10 8 cells/mL to undetectable while the viable cell count was still 10 5 cells/mL. The biphenyl degradation efficiency of stressed TG9 dropped by 50% compared to that of cells at logarithmic phase. During heat stress, the respiratory activity of TG9 declined dramatically while the intracellular ATP level initially increased and then decreased. Notably, the corresponding indicators recovered when restored to 30 °C. These characteristics were in consistent with bacteria entering into VBNC state. Furthermore, fluorescence activated cell sorting together with single cell as seed culture detection verified the unculturability and viability of VBNC state of TG9 cells. Also, we found that single cells in VBNC state could resuscitate and regrowth with significantly extended lag phase (LP). Our results highlight the potential of TG9 for microbial remediation and hint LP duration as an indicator for survival state of bacteria. Graphical abstract: Image 1 Highlights: High temperature induced TG9 into VBNC state with low degradation efficiency. The degradation ability of TG9 could recover after resuscitation. Unculturability, resuscitability of VBNC state were revealed at single-cell level. The lag phase could effectively distinguish the physiological state of bacteria.